EFEKTIVITAS MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Muhammad Bayu Al Dhana; Nurullita Astriani; Eka Susilawati (FKIP Universitas Alwashliyah Medan, 2026)
Communication skills are one of the important aspects in mathematics education, which aims to make students more enthusiastic, broad-minded, and focused on a problem. Efforts to improve students' mathematical communication skills include applying appropriate learning models. This study aims to examine the effectiveness of the Numbered Heads Together (NHT) learning model on students' mathematical communication skills. This study adopted a quantitative method through a quasi-experimental design. The population studied consisted of all seventh-grade students at SMP Swasta Dharma Patra Pkl. Susu. Two classes were selected as samples: class VII-1 with 30 students as the experimental class and class VII-2 with 30 students as the control class. The research tool used was an essay test on the topic of quadrilaterals measured by providing pretest and posttest questions. The data analysis process was carried out using the T-test in the SPSS 22 application. The results of the study showed a difference in mathematical communication skills between students who received learning through the Numbered Heads Together (NHT) model and students who received conventional teaching. Based on the results of the T-test at a significance level of 5% with degrees of freedom (dk) = 58, the t-value obtained was 2.589, which exceeds the t-table value of 2.0017. This means that Ho is rejected and Ha is accepted. Therefore, it can be concluded that students taught with the Numbered Heads Together (NHT) learning model have better mathematical communication skills than students taught through conventional learning.